Salmonella Typhimurium Triggered Unilateral Epididymo-Orchitis and Splenomegaly in a Holstein Bull in Assiut, Egypt: A Case Report - Manal A. M. Mahmoud (Pathogens, 2020)
This report illustrates, for the first time, a case of unilateral orchitis and epididymitis in a Holstein-Friesian bull, associated with Salmonella enterica infection (Salmonella enterica serovar Typhimurium). A one and a half-year-old Holstein-Friesian bull had arrived at the Veterinary Hospital of Assiut University suffering from anorexia accompanied with persistent fever, which did not respond to oxytetracycline and flunixin meglumine injection for 15 days. Gross examination revealed left scrotal enlargement (three times its normal size), heat sensation, and induration of the testis and epididymis, which was painful on external palpation. Microbiological and pathological examinations of the left testicle, epididymis, and spleen samples were performed. S. Typhimurium was recovered from the affected tissues and its critical virulence genes (stn, avrA and sopB) were identified. Pathological examination revealed a unilateral necrotizing intratubular pyogranulomatus orchitis and epididymitis with severe peri-orchitis. In addition, splenomegaly with a firm and large whitish nodular capsular structure associated with different stages of granulomatous reaction around the white and red pulp. To the authors’ knowledge, this report is the first isolation of S. Typhimurium from the epididymis and testicles of a Holstein-Friesian bull. These results highlight the importance of including S. Typhimurium among the health disorders associated with stressful situations in bovine with orchitis and or/epididymitis. In Egypt, Salmonella spp. infection as being enzootic with high probability of dissemination should be considered one of genital health problems among cattle farms.